Highland barley vinasse formaldehyde adsorbent as well as preparation method and application thereof

By subjecting highland barley distiller's grains to alkali blanching with NaOH solution, a highland barley distiller's grains formaldehyde adsorbent with high adsorption rate was prepared, which solved the problem of limited adsorption capacity of existing adsorbents and achieved efficient formaldehyde removal.

CN119303549APending Publication Date: 2025-01-14TIBET UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411618028.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The adsorption capacity of existing formaldehyde adsorbents such as bamboo charcoal is limited and easy to saturate, resulting in their adsorption effect on formaldehyde is not ideal.

Method used

By placing highland barley distiller's grains in a NaOH solution and performing alkali blanching treatment, a highland barley distiller's grains formaldehyde adsorbent is prepared. The adsorbent has a loose and porous surface and contains a large amount of C, H elements and hydroxyl groups. It can achieve chemical adsorption and physical adsorption and improve Formaldehyde adsorption rate.

Benefits of technology

The formaldehyde adsorption rate of highland barley distiller's grains formaldehyde adsorbent can reach up to 22.6%, which is significantly better than traditional adsorbents, and through a combination of chemical and physical adsorption, the purpose of efficient formaldehyde removal is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303549A_ABST
    Figure CN119303549A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological adsorbents, and discloses and particularly relates to a highland barley vinasse formaldehyde adsorbent and a preparation method and application thereof.The highland barley vinasse formaldehyde adsorbent is obtained by placing highland barley vinasse in a NaOH solution, increasing the hydroxyl content in the highland barley vinasse through the NaOH solution and conducting alkali blanching treatment at 52-68 DEG C for 13-47 min; the mass volume ratio of the highland barley vinasse to the NaOH solution is 10 g: 50 mL-55 mL; the concentration of the aqueous alkali is 0.1 mol / L to 0.5 mol / L. The highland barley vinasse formaldehyde adsorbent has a good adsorption effect on formaldehyde, and the highest formaldehyde adsorption rate can reach 22.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biosorbents, and particularly relates to a highland barley lees formaldehyde adsorbent and a preparation method and application thereof. Background Art

[0002] Formaldehyde has the chemical formula HCHO and a relative molecular mass of 30.03. It is also called formic aldehyde. It is a naturally occurring organic compound and a colorless irritating gas. It is irritating to the human eyes and nose and is listed as a known human carcinogen. Formaldehyde solution is an organic solvent. Because it has strong bonding ability and is very cheap, it is widely used as an adhesive for boards. Therefore, there is also a saying that there is no glue without formaldehyde. In addition to wooden building materials such as floors and doors, wooden furniture, coatings, and cleaning agents may also contain formaldehyde; even fabric textiles such as curtains and carpets use dyes and additives containing formaldehyde to achieve wrinkle resistance, color protection, and maintain printing and color.

[0003] Formaldehyde is a typical indoor pollutant and is classified as a Class I carcinogen by the World Health Organization's International Agency for Research on Cancer. It has been fully proven that formaldehyde can cause nasopharyngeal cancer, sinus cancer, lung cancer and blood cancer. If the human body is exposed to formaldehyde for a long time, the blood circulation system, reproductive system, nervous system and respiratory system will be seriously harmed, and may even cause death. Therefore, indoor formaldehyde pollution seriously endangers human life, health and safety.

[0004] GB / T 18883-2022 "Indoor Air Quality Standard" requires that the indoor formaldehyde content should not exceed 0.08mg / m 3 Formaldehyde purification usually adopts adsorbents, photocatalysis and biological methods. At present, the main adsorbent is bamboo charcoal. However, bamboo charcoal has limited adsorption capacity and is easily saturated, so its adsorption effect on formaldehyde is not ideal. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a highland barley lees formaldehyde adsorbent and a preparation method and application thereof. The highland barley lees formaldehyde adsorbent is treated with an alkaline blanching solution to obtain a high adsorption effect on formaldehyde.

[0006] To achieve the above objectives, the technical solutions of the present invention are specifically as follows.

[0007] The first aspect of the present invention provides a highland barley vinasse formaldehyde adsorbent, wherein the highland barley vinasse formaldehyde adsorbent is obtained by placing highland barley vinasse in a NaOH solution, using the NaOH solution to increase the hydroxyl content in the highland barley vinasse, and subjecting the highland barley vinasse to an alkali blanching treatment at 52°C to 68°C;

[0008] The mass volume ratio of the highland barley lees to the NaOH solution is 10 g: 50 mL to 55 mL;

[0009] The concentration of the NaOH solution is 0.1 mol / L to 0.5 mol / L.

[0010] The invention utilizes NaOH solution to modify highland barley vinasse, and controls the concentration of the NaOH solution as well as the time and temperature of the alkaline thermal reaction, so that the surface of the obtained highland barley vinasse formaldehyde adsorbent is loose and porous, and contains a large amount of C, H elements and groups such as hydroxyl groups, thereby being able to simultaneously realize chemical adsorption and physical adsorption, and the adsorption rate of formaldehyde can reach up to 22.6%.

[0011] In another preferred embodiment, the particle size of the highland barley grains formaldehyde adsorbent is 60 mesh to 100 mesh.

[0012] In another preferred embodiment, the step of placing the highland barley lees in the NaOH solution further comprises:

[0013] Steam the highland barley lees and then wash them until they are neutral.

[0014] In another preferred embodiment, the steaming time is 30 min to 33 min.

[0015] The second aspect of the present invention provides a method for preparing the highland barley lees formaldehyde adsorbent, comprising the following steps:

[0016] The highland barley lees are steamed and washed to neutrality, and then mixed with NaOH solution in a mass volume ratio of 10g:50mL-55mL, and subjected to alkaline blanching treatment at 52°C-68°C for 13min-47min, taken out, washed, dried, and crushed to obtain the highland barley lees formaldehyde adsorbent;

[0017] The concentration of the NaOH solution is 0.1 mol / L to 0.5 mol / L.

[0018] The third aspect of the present invention provides a method for removing formaldehyde, which comprises placing the highland barley lees formaldehyde adsorbent in a gas containing formaldehyde, and utilizing the highland barley lees formaldehyde adsorbent to adsorb formaldehyde to remove the formaldehyde.

[0019] In another preferred embodiment, the adsorption temperature is 24°C to 28°C.

[0020] In another preferred embodiment, the adsorption time is 30 min to 150 min.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The highland barley lees formaldehyde adsorbent of the present invention has a good adsorption effect on formaldehyde. The surface of the highland barley lees formaldehyde adsorbent is loose and porous, contains a large amount of C and H elements, and groups such as hydroxyl groups participate in the adsorption process. The adsorption rate of formaldehyde by the highland barley lees formaldehyde adsorbent of the present invention can reach up to 22.6%.

[0023] (2) The present invention explores the adsorption type of highland barley lees formaldehyde adsorbent and finds that its adsorption isotherm is more consistent with the Freundlich model, that is, it belongs to the surface multi-molecular layer and multi-site adsorption type. And through adsorption experiments, highland barley lees residue is more consistent with the description of the second-order kinetic equation, mainly chemical adsorption. The highland barley lees formaldehyde adsorbent in the present invention combines chemical and physical adsorption to achieve the purpose of efficiently removing formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a graph showing the effects of NaOH concentration and water bath temperature on the removal rate of formaldehyde adsorbent from highland barley grains.

[0025] Figure 2 This is a graph showing the effect of NaOH concentration on the adsorption effect of highland barley grains formaldehyde adsorbent.

[0026] Figure 3 This is a graph showing the effect of hemicellulase concentration on the adsorption effect of highland barley grains formaldehyde adsorbent.

[0027] Figure 4 This is a graph showing the effect of cellulase concentration on the adsorption effect of highland barley grains formaldehyde adsorbent.

[0028] Figure 5 This is a graph showing the effect of laccase concentration on the adsorption effect of highland barley grains formaldehyde adsorbent.

[0029] Figure 6 This is a graph showing the effect of particle size of highland barley grains formaldehyde adsorbent on formaldehyde adsorption.

[0030] Figure 7 This is a graph showing the effect of the amount of highland barley grains formaldehyde adsorbent added on the formaldehyde adsorption effect.

[0031] Figure 8 This is a diagram showing the effect of adsorption time on formaldehyde adsorption effect.

[0032] Fig. 9 This is a diagram showing the effect of the initial concentration of adsorbed pollutants on the formaldehyde adsorption effect.

[0033] Fig.10 This is a diagram showing the effect of adsorption temperature on formaldehyde adsorption.

[0034] Fig.11The infrared spectra of different highland barley lees, wherein 1 is untreated highland barley lees, 2 is the highland barley lees formaldehyde adsorbent prepared under optimal conditions, and 3 is the highland barley lees formaldehyde adsorbent after adsorption.

[0035] Fig.12 These are electron microscope pictures of different highland barley grains, where A is untreated highland barley grains, B is the highland barley grains formaldehyde adsorbent prepared under optimal conditions, and C is the highland barley grains formaldehyde adsorbent after adsorption.

[0036] Fig.13 This is the effect of formaldehyde concentration on adsorption effect.

[0037] Fig.14 This is the result of Langmuir analysis.

[0038] Fig.15 This is the result of Friedrich's analysis.

[0039] Fig.16 This is the adsorption kinetics curve.

[0040] Fig.17 This is a pseudo-first-order rate equation curve.

[0041] Fig.18 This is a graph of the pseudo-second-order rate equation.

[0042] Fig.19 This is the effect of temperature on the adsorption effect.

[0043] Fig. 20 This is the adsorption thermodynamic curve.

[0044] Fig.21 This is a comparison chart of the adsorption effects of different highland barley grains formaldehyde adsorbents.

[0045] Fig. 22 This is a graph showing the effect of the number of adsorption cycles on the adsorption effect. DETAILED DESCRIPTION

[0046] The following will be combined with the specific embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0048] Highland barley wine, called "Qiang" in Tibetan, is made from highland barley, a main grain produced in the Qinghai-Tibet Plateau. Highland barley wine is the favorite wine of Tibetan people and has a history of thousands of years. Highland barley lees are the waste left after highland barley winemaking. People usually treat them as waste and use them as animal feed. Highland barley wine is a specialty of Tibetan areas and has a huge market demand. The highland barley lees produced contain more lignin and cellulose, and have multiple functional groups. Therefore, modifying highland barley lees can have a good adsorption effect on formaldehyde.

[0049] The present invention utilizes waste highland barley lees to prepare formaldehyde adsorbent material, turns waste highland barley lees into treasure, realizes secondary utilization of resources, and avoids the impact of highland barley lees on the environment, reduces viruses and bacteria generated by the decay of highland barley lees garbage, and reduces the burden of environmental pollution, which has great theoretical and practical significance. The highland barley lees formaldehyde adsorbent obtained by the present invention through an alkaline solution such as sodium hydroxide under alkali-thermal reaction has a large number of hydroxyls, thereby effectively improving the adsorption effect on formaldehyde, and proves through adsorption isotherms that the highland barley lees formaldehyde adsorbent belongs to the surface multi-molecular layer and multi-site adsorption type, and its main adsorption process is chemical adsorption, that is, it is explained that the highland barley lees formaldehyde adsorbent in the present invention is physical adsorption and chemical adsorption are carried out simultaneously, so it has a better adsorption effect than the adsorbent in the prior art.

[0050] The highland barley lees in the following examples were collected in Tibet.

[0051] Sodium hydroxide (analytical grade) was purchased from Tianjin New Technology Industrial Park Kemao Chemical Reagent Co., Ltd.; oxalic acid (analytical grade) and ethyl acetate (analytical grade) were purchased from Tianjin Yongda Chemical Reagent Co., Ltd.; citric acid (analytical grade) was purchased from Tianjin Ruijinte Chemical Co., Ltd.; bamboo charcoal was purchased from Tianjin Likang Environmental Protection Technology Co., Ltd.; resin (analytical grade) was purchased from Fuzhou Likang Environmental Protection Technology Co., Ltd.; activated carbon (analytical grade) was purchased from Qingdao Yuansheng Activated Carbon Co., Ltd.; diatomaceous earth (analytical grade) was purchased from Tangyin Yusheng Activated Carbon Manufacturing Co., Ltd.; formaldehyde solution was purchased from Luoyang Chemical Reagent.

[0052] Example 1

[0053] A highland barley lees formaldehyde adsorbent comprises the following steps:

[0054] S1. Steam the dried highland barley lees in boiling water for 30 min, and rinse the steamed highland barley lees with water until the pH value is 7 to obtain the treated highland barley lees.

[0055] S2. The treated highland barley lees were mixed with 0.1 mol / L NaOH solution in a mass volume ratio of 10 g:50 mL, and the mixture was bathed in a 60°C water bath for 30 min. After being taken out and cleaned, the mixture was dried in a drying oven at 80°C to constant weight, and then crushed to obtain a 60-mesh highland barley lees formaldehyde adsorbent.

[0056] Example 2

[0057] A highland barley lees formaldehyde adsorbent comprises the following steps:

[0058] S1. Steaming the dried highland barley lees in boiling water for 33 minutes, and washing the steamed highland barley lees with water until the pH value is 7 to obtain treated highland barley lees.

[0059] S2. The treated highland barley lees were mixed with 0.3 mol / L NaOH solution in a mass volume ratio of 10 g:55 mL, and the mixture was bathed in a 52°C water bath for 47 min. After being taken out and cleaned, the mixture was dried in a drying oven at 80°C to constant weight, and then crushed to obtain a highland barley lees formaldehyde adsorbent of 80 mesh.

[0060] Example 3

[0061] A highland barley lees formaldehyde adsorbent comprises the following steps:

[0062] S1. Steam the dried highland barley lees in boiling water for 30 min, and rinse the steamed highland barley lees with water until the pH value is 7 to obtain the treated highland barley lees.

[0063] S2. The treated highland barley lees were mixed with 0.5 mol / L NaOH solution in a mass volume ratio of 10 g:50 mL, and the mixture was bathed in a 68°C water bath for 13 min. After being taken out and cleaned, the mixture was dried in a drying oven at 80°C to constant weight, and then crushed to obtain a 100-mesh highland barley lees formaldehyde adsorbent.

[0064] In order to further illustrate the adsorption effect of the highland barley lees formaldehyde adsorbent of the present invention, the following experiments were conducted.

[0065] 1. Optimization of preparation conditions of highland barley lees formaldehyde adsorbent

[0066] 1) Determine three factors that affect the optimal modification method, set the optimal preparation conditions as the zero level, and use this as the center to develop a three-factor five-level coding table (see Table 1) and a quadratic regression orthogonal rotation combination design table (see Table 2).

[0067] Table 1 Horizontal coding table

[0068] Horizontal Code Value <![CDATA[X1: Sodium hydroxide concentration]]> <![CDATA[X2: Water bath temperature (°C)]]> <![CDATA[X3: Bathing time (min)]]> 1.682 0.25 52 13 1 0.27 55 20 0 0.3 60 30 -1 0.33 65 40 -1.682 0.35 68 47 Horizontal interval value 0.03 5 10

[0069] The statistical analysis by DPS software is shown in Table 2. According to Table 2, 23 kinds of highland barley lees formaldehyde adsorbents were prepared and tested 23 times, and the removal rate was calculated. DPS software can infer the optimal preparation conditions and removal rate prediction, and thus highland barley lees formaldehyde adsorbents were prepared, and the predicted values ​​were verified with the measured values.

[0070] Table 2 Quadratic regression orthogonal rotation combination design table

[0071]

[0072]

[0073] The DPS software was used to perform statistical analysis on the test results in Table 2, and the preliminary regression equation was obtained:

[0074] Y=19.00110-0.51272X1-0.26007X2-0.31399X3-0.27174X 12 -0.40885X 22 -0.7225

[0075] 2X 32 -0.71625X1X2+0.32625X1X3+0.32875X2X3.

[0076] It can be seen from Table 3 that when the significance level is 0.05, the F1=Flack-of-fit in the model is 3.401<F0.05(5,8)=3.69, that is, the difference in the lack-of-fit term is not significant and the overall regression relationship reaches an extremely significant level, indicating that the regression equation model is suitable for the actual situation and its prediction results are highly reliable; the F2=Fregression in the model is 4.753>F0.01(9,13)=4.19, that is, the regression term is extremely significant at the 0.01 level, indicating that this model has a fairly high accuracy and can be used for experimental prediction.

[0077] Table 3 ANOVA

[0078]

[0079]

[0080] Note: SS stands for the sum of squares of deviations, df stands for degrees of freedom, MS stands for mean square, F stands for the ratio of the mean square between groups to the mean square within groups, P stands for significant difference, - stands for the exclusion of the item, and the meanings in the following tables are the same.

[0081] Through a variance analysis, we can see from Table 3 that X1, X 22 There is a significant difference between X1 and X2 at the 0.01 level. 32The difference is significant at the 0.05 level. Since the design is orthogonal, there is no correlation between the regression coefficients. At the α=0.10 level, the insignificant items can be eliminated, and the quadratic analysis of variance is shown in Table 4. The simplified regression equation is constructed: Y=19.00110-0.51272X1-0.40885X 22 +0.72252X 32 -0.71625X1X2.

[0082] Table 4 Quadratic ANOVA

[0083] Sources of variation SS df MS F P X1 3.5902 1 3.5902 6.4387 0.0248 X22 2.7458 1 2.7458 4.9243 0.0449 X32 8.3172 1 8.3172 14.9163 0.002 X1X2 4.1041 1 4.1041 7.3604 0.0178 return 23.8518 9 2.6502 F2=4.753 0.0123 Remaining 7.2487 13 0.5576 - - sum 31.1005 22 - - -

[0084] 2) Single factor effect analysis

[0085] The effects of three single factors on the removal rate are shown in Table 5.

[0086] Table 5 Effect of single factor on removal rate

[0087] level <![CDATA[X1(%)]]> <![CDATA[X2(%)]]> <![CDATA[X3(%)]]> -1.682 19.863 17.845 21.045 -1.341 19.689 18.266 20.300 -1 19.514 18.592 19.724 -0.5 19.257 18.899 19.182 0 19.001 19.001 19.001 0.5 18.745 18.899 19.182 1 18.488 18.592 19.724 1.341 18.314 18.266 20.300 1.682 18.139 17.845 21.045

[0088] It can be seen from Table 5 that X1 is the NaOH concentration. The greater the NaOH concentration, the smaller the removal rate, and the maximum removal rate is 19.863%; X2 is the water bath temperature. The relationship between the removal rate and the water bath temperature is approximately parabolic. The removal rate increases first and then decreases with the increase of the water bath temperature. The maximum removal rate is 19%; X3 is the water bath time. The relationship between the removal rate and the water bath time is approximately parabolic. The removal rate decreases first and then increases with the increase of the water bath temperature. The maximum removal rate is 21.045%.

[0089] 3) Two-factor interaction effect

[0090] From the first analysis of variance, it can be seen that the interactions between the three factors will affect the adsorption effect. Compared with the interactions between X2X3 and X1X3, the X1X2 interaction is extremely significant (P<0.01), that is, the effect of sodium hydroxide concentration and water bath temperature on the adsorption effect is extremely significant. The effect of the interaction between X1X2 is shown in Table 6. The 3D diagram of the interaction relationship between X1X2 is shown in Table 6. Figure 1 .

[0091] Table 6 Effect of NaOH concentration and water bath temperature on removal rate

[0092] level -1.682 -1.341 -1 -0.5 0 0.5 1 1.341 1.682 1.682 19.0083 9.0189 18.9345 18.6389 18.1388 17.4343 16.5254 15.7885 14.9565 1.341 18.7724 18.8663 18.8652 18.6916 18.3136 17.7312 16.9443 16.2906 15.542 1 18.5365 18.7137 18.7958 18.7443 18.4884 18.028 17.3633 16.7928 16.1274 0.5 18.1906 18.4898 18.694 18.8216 18.7447 18.4635 17.9778 17.5294 16.986 0 17.8447 18.266 18.5922 18.8989 19.0011 18.8989 18.5922 18.266 17.8447 -0.5 17.4988 18.0421 18.4905 18.9762 19.2575 19.3343 19.2067 19.0025 18.7033 -1 17.1528 17.8183 18.3887 19.0535 19.5138 19.7697 19.8212 19.7391 19.562 -1.341 16.917 17.6657 18.3193 19.1062 19.6886 20.0666 20.2402 20.2413 20.1474 -1.682 16.6811 17.5131 18.25 19.1589 19.8634 20.3635 20.6591 20.7435 20.7328

[0093] from Figure 1It can be seen that under the same NaOH concentration, the removal rate of highland barley lees formaldehyde adsorbent increases with increasing water bath temperature; the removal rate of highland barley lees formaldehyde adsorbent increases with keeping the water bath temperature unchanged and reducing the NaOH concentration. In summary, the maximum removal rate is 20.7435% under 0.27 mol / L NaOH and 65°C water bath conditions.

[0094] The DPS software predicted the best preparation conditions for alkaline blanching: X1 is -1.682, X2 is 1.682, and X3 is -1.682. At this time, the removal rate of highland barley lees formaldehyde adsorbent is the largest, which is 22.78%. The predicted results are verified. Under the conditions of alkaline blanching sodium hydroxide concentration of 0.27 mol / L, water bath temperature of 65 ° C, and water bath time of 13 min, highland barley lees formaldehyde adsorbent is prepared. The adsorption test is repeated 5 times, and the average removal rate is 22.6%. The ratio of the predicted value to the measured value is 0.992, which is approximately equal to 1, that is, the actual value is consistent with the predicted value, indicating that the model is highly reliable.

[0095] 2. Adsorption effect of different highland barley lees formaldehyde adsorbents

[0096] 1) Alkali blanching method

[0097] Weigh highland barley lees dried to a constant temperature in a drying oven, and weigh 5 portions of 10 g of residue; respectively put five portions of highland barley lees into 100°C water and cook for 30 minutes, immediately rinse the cooked highland barley lees under running water until it is neutral, i.e., pH 7, and respectively put the rinsed highland barley lees into 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, and 0.5 mol / L NaOH solutions, and bathe them in a 60°C water bath for 30 minutes; put the rinsed highland barley lees into a drying oven at 80°C and dry them to constant weight; crush the dried highland barley lees with a pulverizer; and sieve the crushed residue through a 60-mesh sieve for standby use.

[0098] 2) Citrate-assisted hemicellulase

[0099] Weigh the highland barley lees dried to a constant temperature in a drying oven, weigh 5 portions of 10g of the residue; put the 5 portions of highland barley lees residues into 100°C water and cook for 30min; immediately rinse the cooked highland barley lees under running water until the pH is neutral, i.e., 7; put the rinsed highland barley lees into a 0.15mol / L citric acid solution and soak at room temperature for 30min; take out and rinse, and separate the rinsed highland barley lees into a 0.15mol / L citric acid solution; Put it in 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L hemicellulase solution, and bathe it in a 50℃ water bath for 30min; inactivate the enzyme in a 70℃ water bath for 20min; dry the rinsed highland barley lees in a drying oven at 80℃ to constant weight; crush the dried highland barley lees with a grinder; pass the crushed residue through a 60-mesh sieve for later use.

[0100] 3) Ethyl acetate assisted cellulase

[0101] Weigh highland barley lees dried to a constant temperature in a drying oven, and weigh 5 portions of 10g of residue; put 5 portions of highland barley lees residues into 100℃ water and cook for 30min respectively; immediately rinse the cooked highland barley lees under running water until neutral; put the rinsed highland barley lees into 0.15mol / L ethyl acetate solution respectively, and soak at room temperature for 24h; put the rinsed highland barley lees into 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, and 0.5g / L cellulase solutions respectively, and bathe in a 50℃ water bath for 30min; inactivate the enzyme in the highland barley lees in a 70℃ water bath for 10min; put the rinsed highland barley lees into a drying oven at 80℃ and dry to constant weight; crush the dried highland barley lees with a pulverizer; and pass the crushed residue through a 60-mesh sieve for standby use.

[0102] 4) Microwave oxalate-assisted laccase

[0103] Weigh highland barley lees dried to a constant temperature in a drying oven, and weigh 5 portions of 10g of residue; put 5 portions of highland barley lees residue into 100℃ water and cook for 30min respectively; immediately rinse the cooked highland barley lees under running water until neutral; put the rinsed highland barley lees into 0.1mol / L oxalic acid solution respectively, and soak them in a microwave for 15min; put the rinsed highland barley lees into 1g / L, 2g / L, 3g / L, 4g / L, and 5g / L laccase solutions respectively, and bathe them in a 50℃ water bath for 30min; inactivate the enzyme in the highland barley lees residue in an 80℃ water bath for 10min; put the rinsed highland barley lees into a drying oven at 80℃ and dry them to constant weight; crush the dried highland barley lees with a pulverizer; and pass the crushed residue through a 60-mesh sieve for standby use.

[0104] Weigh 1 g of the highland barley lees formaldehyde adsorbent obtained by the above different treatment methods and test it at a formaldehyde concentration of 1.6 mg / m 3The removal rate was measured in a closed box, and the average value was taken after repeated experiments. The results are as follows Figure 2 to Figure 5 shown.

[0105] from Figure 2 to Figure 5 It can be seen that by comparing the formaldehyde adsorbents of highland barley grains obtained by the four methods, the adsorption effects are as follows: alkali blanching method, ethyl acetate-assisted cellulase method, citric acid-assisted hemicellulase method, and microwave oxalic acid-assisted laccase method, indicating that the highland barley grains treated with alkali blanching method have the best adsorption effect on formaldehyde.

[0106] 3. Analysis of formaldehyde removal rate

[0107] According to the optimal combination scheme obtained in 1, the highland barley lees formaldehyde adsorbent was prepared. When conducting a single factor experiment, the levels of other factors are required to be constant, and the five factors of highland barley lees formaldehyde adsorbent particle size, addition amount, adsorption temperature, adsorption time, and initial formaldehyde concentration are studied, and adsorption tests are carried out with different gradients.

[0108] 1) Effect of particle size of highland barley lees formaldehyde adsorbent on adsorption effect

[0109] The highland barley lees formaldehyde adsorbent was sieved through 18 mesh, 40 mesh, 60 mesh, 80 mesh and 100 mesh sieves respectively, and 1g of highland barley lees formaldehyde adsorbent with different mesh sizes was weighed and added into 5 culture dishes respectively. 3 , adsorption was carried out for 30 minutes at 25°C, and the removal rate was calculated based on the instrument readings. The results are as follows Figure 6 As shown, from Figure 6 It can be seen that as the particle size increases, the removal rate first increases and then decreases. Comprehensive analysis shows that the adsorption performance of formaldehyde by highland barley lees formaldehyde adsorbents with different particle sizes is extremely different. The significance is highest when the slag particle size is 80 mesh, but because the difference between 60 mesh and 80 mesh is very small, 60 mesh is selected to avoid waste, F=5638.796 and P<0.01.

[0110] 2) Effect of different addition amounts of modified materials on adsorption effect

[0111] Weigh 1g, 1.5g, 2g, 2.5g, and 3g of highland barley lees formaldehyde adsorbent respectively and add them into 5 culture dishes. 3 , adsorption was carried out for 30 minutes at 25°C, and the removal rate was calculated based on the instrument readings. The results are as follows Figure 7 As shown, from Figure 7 It can be seen that the removal rate initially increases slightly with the increase in the amount of slag added. When the slag is added to a certain mass, the removal rate decreases, and the removal rates of different grams are not much different. Therefore, 1g is selected as the addition amount, F=438.248 and P<0.01.

[0112] 3) Effect of different temperatures on formaldehyde adsorption

[0113] Weigh 1g of highland barley lees formaldehyde adsorbent respectively, and test it at temperatures of 24℃, 25℃, 26℃, 27℃, and 28℃, with a formaldehyde concentration of 1.8mg / m 3 , adsorb for 30 minutes, and calculate the removal rate based on the instrument readings. Figure 8 As shown, from Figure 8 It can be seen that the adsorption effect of highland barley lees on formaldehyde increases with the increase of adsorption time. When the adsorption time is 150 minutes, the removal rate reaches the peak and the adsorption effect is the best. When the adsorption time is 150 minutes, the adsorption effect is the best, F = 66.691 and P < 0.01.

[0114] 4) Effect of pollutant concentration on adsorption effect

[0115] Weigh 1g of highland barley lees formaldehyde adsorbent respectively, so that the pollutant concentration is 0.8mg / m 3 , 1.2mg / m 3 , 1.6mg / m 3 , 2.0mg / m 3 , 2.4mg / m 3 , temperature is 25℃, adsorption is 30min, and the removal rate is calculated based on the instrument readings. The results are as follows Fig. 9 As shown, from Fig. 9 It can be seen that the adsorption effect of highland barley lees on formaldehyde first increases and then decreases with the increase of pollutant concentration. The pollutant concentration is 1.6 mg / m 3 When the removal rate reaches the peak value, the adsorption effect is the best, which is lower or higher than 1.6 mg / m 3 The removal rate will be reduced. The pollutant concentration is 1.6 mg / m 3 When , the adsorption capacity is the strongest, F = 2177.743 and P < 0.01.

[0116] 5) Effect of time on formaldehyde adsorption

[0117] Weigh 1g of highland barley lees formaldehyde adsorbent respectively, and at a formaldehyde concentration of 1.6mg / m 3 When the temperature is 25℃, the adsorption is carried out for 30min, 60min, 90min, 120min and 150min respectively. The removal rate is calculated according to the instrument readings. Fig.10 As shown, from Fig.10 It can be seen that the adsorption effect of highland barley lees formaldehyde adsorbent on formaldehyde increases first and then decreases with the increase of temperature. When the adsorption temperature is 27℃, the removal rate reaches the peak and the adsorption effect is the best. The removal rate will decrease when it is lower or higher than 27℃. When the adsorption temperature is 27℃, the adsorption effect on formaldehyde is the best, F=401.727 and P<0.01.

[0118] 4. Characterization analysis and adsorption mechanism analysis

[0119] 1) Elemental analysis

[0120] Elemental analysis was performed on the untreated highland barley lees, the highland barley lees formaldehyde adsorbent, and the highland barley lees formaldehyde adsorbent after adsorption of formaldehyde. The results are shown in Table 7.

[0121] Table 7 Elemental analysis of three materials

[0122]

[0123] As can be seen from Table 7, the untreated highland barley lees contain more C and H elements, while the S and N elements are relatively small; the C and H contents of the highland barley lees formaldehyde adsorbent increased, indicating that the contents of C and H elements increased after the material was treated with alkali blanching; the C element decreased after adsorption, which played a certain role in the adsorption process.

[0124] 2) Infrared spectroscopy analysis

[0125] The untreated highland barley lees, highland barley lees formaldehyde adsorbent, and highland barley lees formaldehyde adsorbent after adsorption of formaldehyde were measured by infrared spectroscopy. The results are as follows: Fig.11 As shown. Fig.11 It can be seen that there are many groups in highland barley lees, among which hydroxyl groups are significantly increased in highland barley lees formaldehyde adsorbent, with the largest peak; 3500cm -1 The hydroxyl group at the position was greatly shifted, which proved that the hydroxyl group changed after the highland barley grains formaldehyde adsorbent adsorbed formaldehyde, which played a great role in the adsorption.

[0126] 3) Scanning electron microscopy analysis

[0127] The untreated highland barley lees, highland barley lees formaldehyde adsorbent, and highland barley lees formaldehyde adsorbent after adsorption of formaldehyde were analyzed by scanning electron microscope. Fig.12 As shown. Fig.12 It can be seen that compared with the untreated highland barley lees, the highland barley lees formaldehyde adsorbent presents a loose and porous morphology, and the overall surface is rougher. This structure can provide more implantation sites for the adsorption process. The surface of the highland barley lees formaldehyde adsorbent after adsorption is no longer loose, and the surface is smoother than that of the unmodified and modified unadsorbed ones. This is because the loose microporous structure is filled with the adsorbent during the adsorption process.

[0128] 4) Specific surface area and pore size analyzer analysis

[0129] Through the BET experiment, the specific surface area and pore volume of the highland barley lees formaldehyde adsorbent were measured to obtain the specific surface area parameters of the material, which can intuitively illustrate that the highland barley lees formaldehyde adsorbent has a larger pore size and can provide adsorption sites. The results are shown in Table 8.

[0130] Table 8 Specific surface area and pore size analysis

[0131] Test items Modified highland barley grains <![CDATA[Specific surface area (m 2 / g)]]> 3.8621 <![CDATA[Pore volume (cm 3 / g)]]> 0.0093 Pore ​​size distribution (μm) 4.0012

[0132] It can be concluded from Table 8 that the formaldehyde adsorbent from barley lees is a porous material with a large specific surface area and strong activity, and has a strong adsorption capacity.

[0133] 5) Adsorption mechanism analysis

[0134] Adsorption isotherm

[0135] Langmuir and Freundlich isotherm models were used for adsorption equilibrium analysis.

[0136] The Langmuir isotherm is:

[0137] The Freundlich isotherm can be expressed as: q = k·C2 1 / n Formula (2);

[0138] Taking the logarithm of both sides of formula (2) we get:

[0139] lgq=lgk+(1 / n)lgc Formula (3);

[0140] Where: C1 and C2 represent the gas concentration after adsorption, in mg / L; q represents the adsorption amount, in mg / g; q m represents the equilibrium adsorption amount, the unit is mg / g; b represents the adsorption equilibrium constant, the unit is L / mg; k is the isothermal adsorption constant; n in 1 / n represents the isothermal adsorption index.

[0141] The data of initial pollutant concentration and adsorption amount obtained in the single factor experiment are analyzed and sorted, and the adsorption isotherm diagram is drawn, such as Fig.13 As shown, Fig.13 The obtained data were analyzed and collated, and fitted with the Langmuir and Freundlich isotherms to obtain Fig.14 and Fig.15 . And find out the corresponding parameters, as shown in Table 9.

[0142] Table 9 Langmuir and Freundlich model parameters

[0143]

[0144]

[0145] From Table 9, we can see that the Freundlich isotherm R2 As high as 0.9582, it fits better with the corresponding experimental data. It also proves that the adsorption behavior of formaldehyde by highland barley grains is multi-molecular layer and multi-active site adsorption. 1 / n is used as the adsorption intensity index, and 1 / n=0.6819<1 proves that the reaction is relatively easy to occur.

[0146] Adsorption kinetics curve

[0147] The pseudo-first-order kinetic equation is shown in formula (4):

[0148] lg(q e -q t ) = lgq e -k1t / 2.303 formula (4);

[0149] The pseudo-second-order kinetic equation is shown in formula (5):

[0150]

[0151] Where: t represents time, the unit is min; q t Refers to the adsorption amount at time t, in mg / g; q e represents the equilibrium adsorption capacity, in mg / g; k1 represents the first-order adsorption kinetic constant, in min -1 , k2 represents the secondary adsorption kinetic constant, in g·mg -1 ·min -1 .

[0152] Combine the relevant data of equilibrium adsorption amount and adsorption time, and use them as the horizontal and vertical coordinates to draw the kinetic curve, such as Fig.16 As shown, from Fig.16 The adsorption time and adsorption amount are linear, and the longer the time, the greater the adsorption amount; the data in the figure conform to the pseudo-first-order kinetic equation and the pseudo-second-order kinetic equation. Fig.17 , Fig.18 And the corresponding parameters are calculated, as shown in Table 10.

[0153] Table 10 Pseudo-first-order and pseudo-second-order kinetic parameters

[0154]

[0155] As shown in Table 10, the fitting degree with the mathematical model of the quasi-secondary power curve is higher, reaching R 2 =0.9998, which proves that chemical reaction plays a leading role in the adsorption process. The initial concentration measured in the experiment is 2.4 mg / m 3 After 24 hours, the formaldehyde concentration dropped to 0.06 mg / m 3 , reaching the national standard <0.08mg / m 3 standards.

[0156] Adsorption thermodynamics

[0157] The adsorption thermodynamic parameters are calculated as shown in formula (6) to (8):

[0158]

[0159]

[0160] Wherein, ΔG represents the Gibbs free energy change of adsorption, and its unit is kJ / mol; ΔH represents the enthalpy change of adsorption, and its unit is kJ / mol; ΔS represents the entropy change of adsorption, and its unit is J / (mol·K); R is the ideal gas constant, which is 8.314 J / (mol·K); and T represents the time, and its unit is s.

[0161] The adsorption thermodynamic results are shown in Fig.19 and Fig. 20 The thermodynamic parameters of formaldehyde adsorption on highland barley grains are shown in Table 11.

[0162] Table 11 Thermodynamic parameters

[0163] T(K) <![CDATA[ΔG0(KJ / mol)]]> <![CDATA[ΔH0((KJ / mol)]]> <![CDATA[ΔS0(J·mol -1 ·K -1 )]]> 297 -7.66515 29.69345 125.7576 298 -7.76827 29.69345 125.7576 299 -7.88559 29.69345 125.7576 300 -8.08196 29.69345 125.7576 301 -8.13702 29.69345 125.7576

[0164] From Table 11, we can see that △H0>0, the adsorption mode is absorption, △G0<0, indicating that the adsorption is spontaneous; Fig. 20 It can be seen that the correlation coefficient R 2 It is 0.965, which is about 1. The adsorption process conforms to the law of thermodynamic model. It can be judged that the number of effective functional groups on the surface of highland barley lees formaldehyde adsorbent increases, thereby improving the adsorption effect of formaldehyde.

[0165] 5. Adsorption effect of different adsorbents on formaldehyde

[0166] At a temperature of 25°C, the formaldehyde concentration is 1.8 mg / m 3 Under the environment of , highland barley lees, highland barley lees formaldehyde adsorbent, bamboo charcoal, activated carbon, diatomaceous earth, and resin were used for adsorption test. 1g of each adsorption material was taken, and the adsorption time gradient was set to 30min, 60min, 90min, 120min, and 150min. Each adsorption material was tested 3 times with different gradients, and its average removal rate was calculated to compare the adsorption effect. The results are as follows Fig.21 As shown. Among them, the macroporous adsorption resin AB-8 is white granular, with a particle size of 18 mesh; the activated carbon particle size is 60 mesh; the diatomaceous earth particle size is 325 mesh; the bamboo charcoal particle size is 60 mesh; the highland barley lees formaldehyde adsorbent particle size is 60 mesh; the highland barley lees particle size is 60 mesh.

[0167] Depend on Fig.21The comparison shows that the adsorption effects of the six materials are ranked in order of highland barley lees formaldehyde adsorbent, bamboo charcoal, diatomaceous earth, activated carbon, resin, and highland barley lees. Among them, the adsorption effect of highland barley lees formaldehyde adsorbent is the most outstanding compared with the adsorption effects of the other five materials. Among the six different materials, highland barley lees formaldehyde adsorbent has an extremely outstanding adsorption effect, which is significantly better than the other five adsorption materials, F=130224.392 and P<0.01.

[0168] 6. Cycle adsorption times

[0169] The formaldehyde adsorbent of highland barley lees was divided into 3 groups for adsorption test at room temperature of 27℃. After each adsorption for 30 minutes, it was exposed to the sun and then adsorbed again. This was repeated 6 times. The removal rate of each time was calculated and the average value of each group was taken. Fig. 22 .

[0170] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0171] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A highland barley lees formaldehyde adsorbent, characterized in that: The highland barley lees formaldehyde adsorbent is obtained by placing highland barley lees in a NaOH solution, using the NaOH solution to increase the hydroxyl content in the highland barley lees, and performing an alkali blanching treatment at 52°C to 68°C. The mass volume ratio of the highland barley lees to the NaOH solution is 10 g: 50 mL to 55 mL; The concentration of the NaOH solution is 0.1 mol / L to 0.5 mol / L.

2. The method for preparing the highland barley lees formaldehyde adsorbent according to claim 1, characterized in that: The particle size of the highland barley lees formaldehyde adsorbent is 60 meshes to 100 meshes.

3. The method for preparing the highland barley lees formaldehyde adsorbent according to claim 1, characterized in that: The highland barley lees before being placed in the NaOH solution also include: Steam the highland barley lees and then wash them until they are neutral.

4. The method for preparing the highland barley lees formaldehyde adsorbent according to claim 3, characterized in that: The hot steaming time is 30 minutes to 33 minutes.

5. The method for preparing the highland barley lees formaldehyde adsorbent according to any one of claims 1 to 4, characterized in that: The following steps are involved: The highland barley lees are steamed and washed to neutrality, and then mixed with NaOH solution in a mass volume ratio of 10g:50mL-55mL, and subjected to alkaline blanching treatment at 52°C-68°C for 13min-47min, and then taken out, washed, dried, and crushed to obtain the highland barley lees formaldehyde adsorbent; The concentration of the NaOH solution is 0.1 mol / L to 0.5 mol / L.

6. A method for removing formaldehyde, characterized in that: The highland barley lees formaldehyde adsorbent according to any one of claims 1 to 4 is placed in a gas containing formaldehyde, and the highland barley lees formaldehyde adsorbent is used to adsorb formaldehyde to remove formaldehyde in the gas.

7. The method for removing formaldehyde according to claim 6, characterized in that: The adsorption temperature is 24°C to 28°C.

8. The method for removing formaldehyde according to claim 6, characterized in that: The adsorption time is 30 min to 150 min.